Smoothed Income Poverty in European Countries - Birgit Kuchler; Jan Goebel (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
The purpose of this paper is to obtain by combining two longitudinal perspectives a more detailed national picture of poverty in the Member States of the European Union, using the first four waves (1994 - 1997) of the European Community Household Panel (ECHP). In addition to this detailed consideration of the time dimension, poverty incidence, poverty gap and poverty intensity are measured. Overall, the ranking across countries and dimensions is relatively robust. Denmark and Portugal differ from the rest of the countries in each dimension. Other exceptions include France and Ireland, where poverty intensity is considerably lower than in the other welfare regimes. The results in terms of the different subgroups of poor individuals, namely transitory, intermittently and persistently poor, emphasize the importance of a more differentiated perspective on poverty, in particular concerning the relationship between social and demographic characteristics and individuals' long-term income situation.
Keywords: N30; I32; D31; 330; smoothed income; poverty; panel data; ECHP; Armut; Einkommensverteilung; Vergleich; EU-Staaten